Tracheal bronchus: a challenge for anaesthesiologists - Patil, Nitin Tanajirao; Pai, Vasudev B.; Rai, Guruprasad D.; Kamath, Ganesh S. (International Journal of Research in Medical Sciences, 2017)
Tracheal bronchus is an aberrant bronchus that arises most often from the right tracheal wall above the carina and is the result of an additional tracheal outgrowth early in embryonic life. The incidence of tracheal bronchus is approximately 0.1-2%. The presence of congenital anomaly of the central airway can be of great significance to anaesthesiologist and though a rare anomaly it can still be a challenge for proper positioning of DLT and establishing OLV in the hands of junior anaesthesiologists. We report a case with tracheal bronchus arising from right tracheal wall diagnosed when we had difficulty in placing the left DLT. Identification of tracheal bronchus on the chest radiograph and CT-scan of chest before surgery is useful. We do strongly recommend as in other reports, giving the patient an alert card indicating the diagnosis of tracheal bronchus.